Processo sucessório em empresas familiares: uma leitura a partir da comunicação organizacional - Rosário, Ivone Maria Correia de Almeida Pires do (2016)
Family and business consists in a complex association involving, simultaneously, the professional area and the personal one. The capacity to deal with feelings and particular interests, which are influencers on the daily routine of the organization, hinders the communication. Personal conflicts produce diverse effects. In this way, the organizational communication, the creation and practice of rules of behavior, the family relationship are some of the aspects that promotes (in) consistency on the business management opening a successful space for the succession process in family businesses. Niklas Luhmann ´s theory of the social systems provided the development of this survey in a way never attempt to in the area of organizational communication when dealing with the theme succession process in family businesses. At the time of the theme delimitation, more than one hundred readings had been made. In order to accomplish the established objectives, first was used the descriptive research. With the development of the state-of-art there was a transition to the interpretative research. This reflection made possible a new view of the corpus been studied, coming from diverse areas of knowledge under the eyes of the organizational communication. From the perspective of the technical process, the bibliographic research analysis was decisive for the state-of-art interdisciplinary search. The qualitative research was chosen to approach the problem in its fullness, which favored a more detailed study of the theme, resulting in theory deep research. Maybe an unexploited aspect by the other areas of knowledge. For these areas, so far, the communication is a tool in this process, acting instrumentally and in a managerial way and not fulfilling and autonomous from the interaction among the social actors in the organizational culture of the company.